Composition and cross-sectional area of muscle fibre types in relation to daily gain and lean and fat content of carcass in Landrace and Yorkshire pigs - Ruusunen, Marita; Sevon-Aimonen, Marja-Liisa; Puolanne, Eero (Agricultural and Food Science, 1996)
The muscle fibre-type properties of longissimus were compared between Landrace and Yorkshire breeds and between the sexes in an attempt to shed light on the relationship of these histochemical parameters to animal growth and carcass composition. Muscle fibres were classified into three groups, type I, type lIA and type 11B, using the myosin ATPase method. At a given live weight, the cross-sectional area of type I fibres (CSA1) was smaller (p<0.01) and the cross-sectional area of type 11B fibres (CSAIIB) larger (p<0.01) in longissimus of Landrace than in that of Yorkshire. The CSAIIB (p<0.01) was larger in gilts than in castrated males. At an average live weight of 97 kg, the Landrace pigs were significantly younger (p<0.01) than the Yorkshire pigs. The pH1 value of Landrace was lower (p<0.01) than that of Yorkshire. The percentage of high-value cuts in carcass with head (M%) was lower (p<0.01) and the percentage of fat in back and loin (F%) higher (p<0.01) in castrated males than in gilts. The cross-sectional area of loin (CSAloin) was larger (p<0.01) in gilts than in castrated males. All the histochemical and other traits varied considerably between the animals. The correlations between histochemical properties and growth and histochemical properties and carcass composition were rather low.